Bulletin of Hispanic Studies: tomo 31 (1954), tomo 32 (1955), tomo 33 (1956), tomo 34 (1957). - T. A. (Nueva Revista de Filología Hispánica, 1971)
Se reseñó: Bulletin of Hispanic Studies: tomo 31 (1954), tomo 32 (1955), tomo 33 (1956), tomo 34 (1957).